Analyses on Prestress Loss and Flexural Performance of the Laminated Bamboo Beam Applied with Prestressed BFRP Sheet. (30th April 2019) - Lv, Qingfang; Liu, Ye; Ding, Yi
Abstract : Inspired by the studies about wooden beam applied with prestressed steel plate and bamboo beam strengthened by fiber-reinforced polymer (FRP), this paper aims to explore the applicability of the prestressed basalt fiber-reinforced polymer (BFRP) sheet to the laminated bamboo beam and the variation of the flexural performance of the laminated bamboo beam applied with prestressed BFRP sheet. Two series of tests were conducted in the present study. In the first series of tests, the prestress loss of the prestressed BFRP sheet was classified and analyzed based on measured strains and deflections, which led to a derivation of the effective prestressed force considering the prestress loss. Analyses showed that the recommended value of prestress loss compared with the initial prestressed force was 22.0% based on the existing test data in the specimen preparation stage. In the second series of tests, the static loading test was performed to investigate the flexural performance of the laminated bamboo beam applied with prestressed BFRP sheet and analyze the difference between the laminated bamboo beams applied with prestressed and non-prestressed BFRP sheets. Test results showed that the no significant variation of the ultimate load and a reduction of the ultimate deformation capacity were caused by the application of the prestressed BFRP sheet.